1985
DOI: 10.1111/j.1748-1716.1985.tb07759.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in isometric force‐ and relaxation‐time, electromyographic and muscle fibre characteristics of human skeletal muscle during strength training and detraining

Abstract: Eleven male subjects (20-32 years) accustomed to strength training went through progressive, high-load strength training for 24 weeks with intensities ranging variably between 70 and 120% during each month. This training was also followed by a 12-week detraining period. An increase of 26.8% (P less than 0.001) in maximal isometric strength took place during the training. The increase in strength correlated (P less than 0.05) with significant (P less than 0.05-0.01) increases in the neural activation (IEMG) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
278
5
24

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(333 citation statements)
references
References 14 publications
26
278
5
24
Order By: Relevance
“…The moderate bivariate correlations between the changes in MVT and agonist EMG in the current study (r = 0.576) were consistent with several previous EMG studies of lower body RT [r = 0.69 (Shima et al 2002); r = 0.74 (Häk-kinen and Komi 1986); r = 0.66 (Häkkinen et al 1985)], but not an elbow flexor RT study (r = 0.187; Erskine et al 2014), which may be significant as the elbow flexors have been found to have a very high level of activation even in the pre-training state (Allen et al 1998;Gandevia et al 1998). In addition, two studies that measured the changes in agonist activation with ITT also found no relationship with individual strength gains after RT (Shima et al 2002;Erskine et al 2010b), although several studies have queried the sensitivity of the ITT to detect changes in activation after RT Harridge et al 1999;Cannon et al 2007;Del Balso and Cafarelli 2007;Tillin et al 2011).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The moderate bivariate correlations between the changes in MVT and agonist EMG in the current study (r = 0.576) were consistent with several previous EMG studies of lower body RT [r = 0.69 (Shima et al 2002); r = 0.74 (Häk-kinen and Komi 1986); r = 0.66 (Häkkinen et al 1985)], but not an elbow flexor RT study (r = 0.187; Erskine et al 2014), which may be significant as the elbow flexors have been found to have a very high level of activation even in the pre-training state (Allen et al 1998;Gandevia et al 1998). In addition, two studies that measured the changes in agonist activation with ITT also found no relationship with individual strength gains after RT (Shima et al 2002;Erskine et al 2010b), although several studies have queried the sensitivity of the ITT to detect changes in activation after RT Harridge et al 1999;Cannon et al 2007;Del Balso and Cafarelli 2007;Tillin et al 2011).…”
Section: Discussionsupporting
confidence: 79%
“…The relationship between the individual changes in strength following training and the putative underpinning neural and morphological adaptations has previously been investigated primarily using bivariate correlations. These studies have reported changes in strength to be both significantly related and unrelated to the changes in neural [significant: agonist electromyography (EMG): r = 0.66-0.74 (Häkkinen et al 1985;Häkkinen and Komi 1986;Shima et al 2002); non-significant: agonist activation assessed with the interpolated twitch technique (ITT): r = −0.124-0.47 (Erskine et al 2010b), antagonist EMG: r = 0.09 (Erskine et al 2010b) or morphological variables [significant: muscle volume assessed via magnetic resonance imaging (MRI): r = 0.48-0.53 (Erskine et al 2014); non-significant: muscle volume assessed via MRI: r = 0.15 (Erskine et al 2010b); muscle fascicle pennation angle (θ p ) assessed via ultrasonography: r = −0.33-0.26 (Nimphius et al 2012)]. Therefore, there is considerable confusion about the contribution of specific physiological variables to the individual changes in strength.…”
Section: Introductionmentioning
confidence: 99%
“…Although not specifically measured, this may be caused from a lack of a behavior change to exercise independently after five months training, which supports previous data [17][18][19]. Prior to beginning this exercise program, all participants were living self-declared sedentary lifestyles.…”
Section: Discussionsupporting
confidence: 60%
“…The early phase of RFD is thought to be determined mainly by the neural drive to the muscle, as well as the muscle fiber type composition [2,[7][8][9]. Late phase RFD is largely influenced by maximal strength and most likely muscle mass, as suggested by studies reporting parallel changes in maximal muscle strength and contractile RFD 150-250 ms from the onset of contraction [1,2,7,8,[10][11][12][13]. Nevertheless, little is known about the correlation between muscle mass and RFD in power athletes.…”
Section: Introductionmentioning
confidence: 99%